Hubungan Citra Merek dan Terpaan Brand Ambassador Dengan Keputusan Pembelian di Blibli - Tasya Nadia; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
The increasing numbers of e-commerce in Indonesia makes competition in marketing activities is getting tougher. Blibli as one of the e-commerce companies in Indonesia that continues to strive to be the first choices e-commerce in the minds of Indonesian consumers. Although it has been established for 10 years, Blibli only placed the fifth position as e-commerce with the highest number of monthly visitors. In order to realize its vision, which is “to become the number one e-commerce company with the largest number of loyal customers”, Blibli continues to build a good image and appoint its newest brand ambassador, Park Seo Jun. This study aims to determine the relationship between brand image and brand ambassador exposure with purchasing decisions at Blibli. This study uses quantitative research methods with an explanatory approach. The data collection technique that used in this study is non-probability sampling with a sample size of 80 respondents. The theory used in this study is the theory of brand image according to Halbheer and Theory of Meaning Transfer. Hypothesis testing using Pearson Correlation with the help of SPSS program. The results of the hypothesis test show that the significance value between brand image (X1) and purchasing decisions in Blibli (Y) is 0.029 and the correlation coefficient value is 0.244, this value indicates that there is a positive relationship between variables. This can be interpreted that the better the brand image owned by Blibli, the higher the purchasing decision at Blibli. While the results of the hypothesis test for the brand ambassador exposure (X2) with the purchase decision at Blibli (Y) is 0.005 and the correlation coefficient value is 0.311. This shows that there is a very significant positive correlation or relationship between the brand ambassador exposure (X2) and the purchasing decision at Blibli (Y).